Bromatological characteristics of the cowpea in the resistance to Callosobruchus maculatus - Pallaoro, Dryelle Sifuentes; Oliveira, Glauce Portela de; Faria, Dayana Aparecida de; Camili, Elisangela Clarete; Caneppele, Maria Aparecida Braga (Comunicata Scientiae, 2019)
This work aimed to relate the bromatological characteristics of four cowpea cultivars to the preference and development of Callosobruchus maculatus. For this, oviposition preference, choice and no-choice tests were performed in four cowpea genotypes: Bico de Ouro, BRS Novaera, BRS Guariba and BRS Tumucumaque. In the no-choice test were determined: viability of eggs, duration of the immature stage, biological cycle, viability of the immature stage, population growth rate, weight per insect, biomass consumption and consumption per insect. As to the chemical composition, the seeds were characterized concerning the crude protein content, ash, neutral detergent fiber, acid detergent fiber and organic matter. In the evaluation, there were significant differences within the genotypes, except for the viability of eggs and consumption per insect. The BRS Novaera genotype presented antixenosis resistance to C. maculatus, whereas the Bico de Ouro, BRS Guariba and BRS Tumucumaque genotypes revealed to be susceptible. The chemical composition of the seeds affects the development of C. maculatus, and the crude protein and ash contents of the seeds without integument present a positive influence over the insect development.